GAMBARAN PERILAKU PERAWAT DALAM MERAWAT PASIEN SECTIO CAESAREA DENGAN HIV/AIDS - Vetry Melinda Opita; Yulia Irvani Dewi; Sofiana " Nurchayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract  Every year, case of HIV/AIDS increases in Indonesia. Most cases were found to men, however women are risky spreading from their partner through sexual activity which causes pregnancy. It is proposed to give sectio caesarea, meanwhile this is really risky treatment for the nurse. The research aimed to describe of nurse’s behaviour in taking care of sectio caesarea patient with HIV/AIDS. This study used descriptive design with cross sectional approach. The number of samples were 51 people with total sampling technique who met criteria of inclusion in operating room RSUD Arifin Achmad Pekanbaru. This study used questionnaires about knowledge, attitude, and action. Data analysis used statistic descriptive. The research showed that the most ages were between 36-45 years (45.1%), Female (66.7%) employee paid by honorarium  (52.9%), diploma III academic degree (92.2%), 5-10 years working and >10 years (41.2%). Based on the good point of assesment about (74.5%), positive attitude (52.9%) and good treatment in taking care of Sectio Caesarea patient with HIV/AIDS (78.4%). The research suggest for nurses in the operating room to improve their knowledge, skills in taking care patient sectio caesarea with HIV/AIDS by following training.  Keywords   : Action, Attitude, HIV/AIDS with Sectio Caesarea, Knowledge, Nurse